Maternal Recreational Exercise during Pregnancy in relation to Children's BMI at 7 Years of Age - Camilla Schou Andersen; Mette Juhl; Michael Gamborg; Thorkild I. A. Sørensen; Ellen Aagaard Nohr (Hindawi Limited, 2012)
Exposures during fetal life may have long-term health consequences including risk of childhood overweight. We investigated the associations between maternal recreational exercise during early and late pregnancy and the children's body mass index (BMI) and risk of overweight at 7 years. Data on 40,280 mother-child pairs from the Danish National Birth Cohort was used. Self-reported information about exercise was obtained from telephone interviews around gestational weeks 16 and 30. Children's weight and height were reported in a 7-year follow-up and used to calculate BMI and overweight status. Data was analyzed using multiple linear and logistic regression models. Recreational exercise across pregnancy was inversely related to children's BMI and risk of overweight, but all associations were mainly explained by smoking habits, socioeconomic status, and maternal pre-pregnancy BMI. Additionally, we did not find exercise intensity or changes in exercise habits in pregnancy related to the children's BMI or risk of overweight.